Motor abilities as predictors in artistic swimming: a cross-sectional study - Aleksic Veljkovic, A.; Stankovic, S.; Katanic, B. (Facta Universitatis: Series Physical Education and Sport, 2021)
The aim of this research was to examine the association between motor abilities and achievement in artistic swimmers at the national competition level. Thirty-five junior synchro swimmers (age 16 to 18 years old, height 165.49±3.57cm, and weight of 53±4.23kg) took part in the research. Motor ability evaluation comprised eleven tests for overall and two tests for specific motor abilities. The data analysis was done in SPSS 20.0. The results show a statistically significant association between the predictor system and the criteria (p=.00). The technical execution score was correlated with several physical fitness variables. A multiple regression analysis revealed that push-ups, balance with open eyes, and T2 accounted for a large part (.69%) of the variance in the final score. The results of this research are practically applicable in more qualitative preparation of synchro swimmers and achieving maximal results.